Methodological Advances in Experimental Philosophy 2019
DOI: 10.5040/9781350069022.ch-003
|View full text |Cite
|
Sign up to set email alerts
|

Eyes as Windows to Minds: Psycholinguistics for Experimental Philosophy

Abstract: Psycholinguistic methods hold great promise for experimental philosophy. Many philosophical thought experiments and arguments proceed from verbal descriptions of possible cases. Many relevant intuitions and conclusions are driven by spontaneous inferences about what else must also be true in the cases described. Such inferences are continually made in language comprehension and production. This chapter explains how methods from psycholinguistics can be employed to study such routine automatic inferences, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 78 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…A forced-choice plausibility ranking experiment (reported in Supplementary Appendix, Section C, to the present paper) confirmed that epistemic agent features are yet more strongly associated with 'aware' than 'see'-where the association is strong enough to support a prominent epistemic use ('I see your point'), arguably interpreted with the common metaphorinterpretation strategy of stereotype-feature transfer (Bortfeld and McGlone 2001;Searle 1993). Plausibility ratings elicited in a comprehension study with eye tracking confirmed that, where contextually irrelevant and unsupported, spatial patient features (X is before S) get completely suppressed in interpreting 'aware' (though not 'see') sentences (Fischer and Engelhardt 2019); this suggests they are weakly associated with 'aware'. We tentatively conclude that, in the 'aware' stereotype, epistemic agent features are very strongly associated with the verb, whereas the other features are weakly associated.…”
Section: Reanalysing the Argument From Illusionmentioning
confidence: 78%
See 2 more Smart Citations
“…A forced-choice plausibility ranking experiment (reported in Supplementary Appendix, Section C, to the present paper) confirmed that epistemic agent features are yet more strongly associated with 'aware' than 'see'-where the association is strong enough to support a prominent epistemic use ('I see your point'), arguably interpreted with the common metaphorinterpretation strategy of stereotype-feature transfer (Bortfeld and McGlone 2001;Searle 1993). Plausibility ratings elicited in a comprehension study with eye tracking confirmed that, where contextually irrelevant and unsupported, spatial patient features (X is before S) get completely suppressed in interpreting 'aware' (though not 'see') sentences (Fischer and Engelhardt 2019); this suggests they are weakly associated with 'aware'. We tentatively conclude that, in the 'aware' stereotype, epistemic agent features are very strongly associated with the verb, whereas the other features are weakly associated.…”
Section: Reanalysing the Argument From Illusionmentioning
confidence: 78%
“…An eye-tracking study revealed extensive similarities in intricate processing patterns for 'aware'-and 'see'-sentences which strongly suggest similar schemas are deployed in interpreting them (Fischer and Engelhardt 2019) with the retention strategy (see above, Sect. 3.1).…”
Section: Reanalysing the Argument From Illusionmentioning
confidence: 95%
See 1 more Smart Citation
“…We wanted to develop a survey that could comprehensively assess a sizable number of non-philosophers' responses with respect to all five of Johnston's core beliefs, so that we could compare participant agreement across them. We encourage researchers to employ many methods, including psycholinguistic methods (Fischer and Engelhardt 2016, 2017, 2019, because the triangulation of data from different methods will certainly yield a richer understanding of folk core beliefs about color.…”
Section: Discussionmentioning
confidence: 99%
“…The first experiments to examine the Salience Bias Hypothesis provided supporting evidence from perception verbs, and illustrate the interplay between these conditions: An eye-tracking study revealed extensive similarities in intricate processing patterns for 'aware'-and 'see'-sentences that strongly suggest similar schemas are deployed in interpreting them (Fischer and Engelhardt 2019b) with the Retention/Suppression strategy [as per condition (ii)]. However, a corpus analysis on random 1000-sentence samples from the British National Corpus confirmed that while the visual use is clearly the most frequent for 'S sees X' (68% of sampled occurrences) [as per (i)], it is far less frequent for 'S is aware of X' (23%) (Fischer and Engelhardt 2017a).…”
Section: Thenmentioning
confidence: 97%